Rubāʿiyyāt-i Ḥakīm Khayyām - al-Khayyām, ʿUmar, (Miras Maktoob, ISBN: 9789004365452., 2019)
The rubāʿī or quatrain is a short Persian poem in a special metre with a rhyme suitable to its form. Its use is not bound to any specific field, there being philosophical, satirical, romantic, lyrical and other types of quatrain. In the past, it was believed that the rubāʿī was a special form of the hazaj metre of Arabic poetry. Meanwhile, it has been established that it is in fact Iranian, its origin being the pre-Islamic tarānah or song for feasting and wine. In the West the quatrain was rendered immortal through the work of ʿUmar al-Khayyām (d. ca. 517/1123). A native of Nishapur, he was a respected mathematician and astronomer, as well as a recognized expert in poetry. Many of the quatrains ascribed to him are, however, spurious. This volume contains a reprint of Yār Aḥmad Rashīdī's selection (dated 867/1460), first published in 1953, followed by two other works in Persian, also by Khayyām.